Tailored Air-Handling System Development for Gasoline Compression Ignition in a Heavy-Duty Diesel Engine - Kumar, Praveen; Zhang, Yu; Traver, Michael; Watson, John (Frontiers in Mechanical Engineering, 2021)
This work presents the analysis-led development of a low-NOx GCI air-handling system including both turbocharger matching and EGR configuration for a prototype heavy-duty GCI engine based on a model year 2013 Cummins ISX diesel engine using a low octane gasoline (RON80). In the analysis-led development process, a 1-D engine system level analysis was closely coupled with closed-cycle 3-D CFD GCI combustion development. Using a validated 1-D engine model, three different boost systems were investigated: (1) the production turbocharger; (2) an off-the-shelf single -stage waste-gate turbocharger; and (3) a prototype single stage variable geometry turbocharger. For each boost system, three EGR configurations were evaluated: (1) a high-pressure EGR route; (2) a low-pressure EGR route; and (3) a dual-loop EGR route. The air-handling system performance was first investigated over five steady-state engine operating conditions extracted from the ramped modal cycle supplemental emissions test. Then, through co-simulation using a Simulink based engine controls model, the best performing candidates under transient operation through the Heavy-Duty Federal Test Procedure certification cycle were identified. The production turbocharger, designed for 4-6 g/kWh engine-out NOx, suffered from low combined turbocharger efficiency under the low NOx GCI thermal boundary conditions. The prototype 1-Stage variable geometry turbocharger, when used with a high pressure EGR configuration, demonstrated higher combined efficiencies while the waste-gate turbocharger showed the best results when used with a dual loop EGR system. All low pressure only EGR configurations were found to incur additional pumping penalties due to the need for a back pressure valve to drive sufficient EGR levels. In the transient test cycle analysis, the single stage high pressure EGR system was capable of delivering the target boost and EGR while the off-the-shelf waste-gate turbocharger, with its higher mass inertia, showed slower turbine response and a resulting lag in boost response. Unsurprisingly, the dual loop EGR system also suffered from delays in EGR delivery during engine acceleration. In summary, the prototype single stage variable geometry turbocharger with a high pressure EGR system produced the best performance and was identified as the best candidate for the prototype low-NOx heavy duty GCI engine.